Application of Turbiscan LAB to study the influence of lignite on the static stability of PCLWS. (15th February 2018) - Ren, Yangguang; Zheng, Jiaxing; Xu, Zhiqiang; Zhang, Yuxing; Zheng, Jianping
Highlights: With the decrease in P/L mass ratio the PCLWS pseudoplasticity and static stability gradually enhanced. The solid concentration of PCLWS with good stability reached about 60 wt% at a P/L mass ratio of 6:4. Turbiscan LAB was employed to characterize the static stability of mixed slurry. The static stability of PCULWS first increased and then decreased along with the lignite upgrade. The oxygen functional groups and side chains of lignite particles supported the composite particles. Abstract: To study the influence of different petcoke/lignite (P/L) mass ratios on the static stability of petcoke/lignite water slurry (PCLWS), Turbiscan Lab was employed to quantitatively and objectively characterize the static stability of mixed slurry. Besides, the effect of microwave irradiating the lignite for different times on the static stability of petcoke/upgraded lignite water slurry (PCULWS) was explored at a P/L mass ratio of 6:4. And the chemical property changes of upgraded lignite were measured through proximate and ultimate analysis and X-ray photoelectron spectra to elucidate the influence of lignite particles on the static stability of mixed slurry. With the decrease in P/L mass ratio the pseudo-plasticity and static stability of PCLWS gradually enhanced. Furthermore, the solid concentration of PCLWS with good static stability reached about 60 wt% at a P/L mass ratio of 6:4. Small decreases in volatile matter, moisture and oxygen functional group content and small increases in fixed carbon of the lignite were associated with an increase in the static stability of PCULWS, but further changes in these properties following prolonged microwave irradiation were associated with a decrease in static stability, perhaps as a result of the destruction of the three-dimensional network of lignite particles. Therefore, the abundant oxygen-containing functional groups and side chains of lignite particles probably plays an indispensable role in supporting the composite particles formed by lignite, petcoke, moisture and dispersant molecules.